KESEGARAN JASMANI SISWA SMAN 1 DANGIA DI MASA PANDEMIK COVID-19 - Resky Ana Abadi; Ika Sartika (Jurnal Penjaskesrek, 2021)
Physical fitness is the ability of a person to carry out his daily duties easily, without feeling excessively tired, and still having leftover or spare energy to enjoy his spare time and for sudden needs. Good physical fitness can increase body immunity during the Covid-19 pandemic. This study used a qualitative descriptive approach to determine the level of physical fitness of students of SMAN 1 Dangia during the Covid-19 pandemic. The sample in this study was 40 students in Kolaka Timur Regency using purposive sampling technique. Physical fitness of the students of SMAN 1 Dangia was in the good category as many as 55% or as many as 22 students, the moderate category was 40% or as many as 16 students and 5% were in the poor category. Abstrak Kesegaran jasmani adalah kemampuan seseorang untuk menunaikan tugasnya sehari-hari dengan mudah, tanpa merasa lelah yang berlebihan, serta masih mempunyai sisa atau cadangan tenaga untuk menikmati waktu senggangnya dan untuk keperluan-keperluan mendadak. Kesegaran jasmani yang baik dapat meningkatkan imunitas tubuh pada masa pandemik covid-19. Penelitian ini menggunakan pendekatan deskriptif kualitatif untuk mengetahui tingkat kesegaran jasmani siswa SMAN 1 Dangia dimasa pandemik covid-19. Sampel dalam penelitian ini adalah 40 siswa di Kabupaten Kolaka Timur dengan menggunakan teknik purposive sampling. Kesegaran jasmani siswa SMAN 1 Dangia masuk dalam kategori baik sebanyak 55% atau sebanyak 22 siswa, kategori sedang sebesar 40% atau sebanyak 16 siswa dan 5% masuk dalam kategori kurang. Kata Kunci: Kesegaran Jasmani, Siswa